Exploiting timely demand information in determining production lot-sizing: an exploratory study. Issue 16 (18th August 2017) - Gu, Qiannong; Visich, John K.; Li, Kunpeng; Wang, Ziping
Abstract : The emerging automatic data-capturing technology, radio frequency identification technology (RFID), has been extensively adopted in logistics process and retail operations. However, limited research has been conducted on how to exploit and integrate RFID-enabled timely demand information into production processes. The lack of sufficient evaluation on the financial benefits of RFID hinders the adoption of this technology in production processes. In this study, we propose a framework to integrate RFID-enabled timely demand information into a dynamic production lot-sizing problem. Our results show that manufacturers, distributors and retailers can benefit from the availability of timely demand information via RFID. Our research sheds new light on understanding the financial value of RFID in a production process, and fills a gap in the application of RFID along the supply chain.